2011
DOI: 10.3109/00365548.2011.616224
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent refractory Clostridium difficile colitis treated successfully with rifaximin and tigecycline: A case report and review of the literature

Abstract: Clostridium difficile colitis infection is on the rise and is considerably increasing the duration of hospital stay, as well as healthcare costs. The management of C. difficile colitis has become more challenging with the increasing failure of therapeutic response to metronidazole and oral vancomycin. Tigecycline is a new glycylcycline that has shown in vitro activity against C. difficile. We report herein a case of C. difficile colitis that failed to improve on a combination of metronidazole and oral vancomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…Garey y cols., en el 2011, en vista de que en series no controladas se había mostrado disminución de las recurrencias con el uso de rifaximina siguiendo terapias habituales, diseñó un ECR doble ciego comparando placebo vs rifaximina al término de una terapia estándar con vancomicina mostrando que las recurrencias con placebo fueron 49 vs 21% con rifaximina 141 . Reportes de casos, revisiones bibliográficas y estudios no controlados 129,[142][143][144][145][146][147][148] coinciden en la utilidad en el uso de rifaximina en recurrencias. La dosis utilizada en los estudios es de 400 mg c/8 h vía oral por 28 días siguiendo a un curso habitual de vancomicina oral.…”
Section: ¿Es úTil El Uso De Rifaximina?unclassified
“…Garey y cols., en el 2011, en vista de que en series no controladas se había mostrado disminución de las recurrencias con el uso de rifaximina siguiendo terapias habituales, diseñó un ECR doble ciego comparando placebo vs rifaximina al término de una terapia estándar con vancomicina mostrando que las recurrencias con placebo fueron 49 vs 21% con rifaximina 141 . Reportes de casos, revisiones bibliográficas y estudios no controlados 129,[142][143][144][145][146][147][148] coinciden en la utilidad en el uso de rifaximina en recurrencias. La dosis utilizada en los estudios es de 400 mg c/8 h vía oral por 28 días siguiendo a un curso habitual de vancomicina oral.…”
Section: ¿Es úTil El Uso De Rifaximina?unclassified
“…It has antimicrobial activity covering gram-positive organisms including MRSA and VRE, gram-negative organisms as well as anaerobic bacteria and is an approved treatment of complex intra-abdominal infections including peritonitis [24,25]. While not standard therapy for CDI, tigecycline has also been shown to have efficacy against C. difficile and has been reported as an effective adjunct for CDI in recent reports [26]. Herpers et al, in a case series demonstrated successful eradication of C. difficile in four severe refractory cases after the addition of IV tigecycline [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been used effectively with vancomycin via simultaneous administration, drug cycling, or sequential monotherapy [7, 8]. Also, El-Herte et al reported a recent case of C. difficile in which the patient initially failed metronidazole and vancomycin therapy, but was successfully treated with a combination of rifaximin and tigecycline [9]. …”
Section: Discussionmentioning
confidence: 99%
“…There have been 8 cases in total, 7 of which were successful in treating refractory CDI using tigecycline as monotherapy [15, 16] or in combination with another antibiotics such as metronidazole [17] or rifaximin [9]. These 7 cases reported patient recovery within one week of therapy without recurrence of symptoms after a 3 month period.…”
Section: Discussionmentioning
confidence: 99%